God Almighty’s Management of the livelihoods of the Worshippers: between the Islamic and the Communist Views - Al Dulaimy , Muayad (Islamic Sciences Journal, 2023)
Different viewpoints are presented in the issue of God’s management of people’s livelihoods and reforming their livelihoods according to the doctrines and trends that make up the overall composition of individuals and societies. Given the existence of a great discrepancy between the two views of the Islamic religion and the communist doctrine on this important ideological issue, the researcher sought to diagnose the origins of this phenomenon and identify its most prominent manifestations, determine its characteristics, describe its nature, and clarify the quality of the relationship between its causes, variables, and trends. Using the descriptive analytical method is intended to provide a comprehensive comparison between these two views.